PENGARUH LAMA PERENDAMAN DALAM PROSES PEMBUATAN AWETAN MANGGA APELL (Mangifera indica) TERHADAP DAYA TERIMA PRODUK - Maemunah, Yati Setiati; Yulianti, Yeni (LPPM, Universitas Negeri Jakarta, 2021)
The purpose of this research is to analyze the influence of immersion in the process of manufacture mango apple (Mangifera indica) on the acceptance of the product. In the research of the effect of long immersion of dried apple mango fruit to the physical quality, sensory of candied apple mango products. This research uses experimental method. The result of consumer acceptance test, product of mango apple with the duration of soaking different from the duration of marinade 3 days, 5 days and 7 days are generally acceptable to the consumer by obtaining the acceptance category scales. The data obtained from the panelist assessment is somewhat trained as many as 30 people result of the research hypothesis indicate that there is influence of receipt of mango product of apple mangoes to consumer acceptance in all aspects ie color, flavor, aroma, and textur. The result of the assessment of consumer's preference level on the duration of soaking preserved apple mango with a long period of soaking for 3 days, 5 days, and 7 days is much preferred is preserved apple mango with 5 days immersion and can be recommended for further production. Keywords: acceptance product, influence, long immersion, mango apple, manufacture.